Characterization of Clinical Absorption, Distribution, Metabolism, and Excretion and Pharmacokinetics of Velsecorat Using an Intravenous Microtracer Combined with an Inhaled Dose in Healthy Subjects - Holmberg, Ann Aurell; Weidolf, Lars; Necander, Sofia; Bold, Peter; Sidhu, Sharan; Pelay-Gimeno, Marta; de Ligt, Rianne A.F.; Verheij, Elwin R.; Jauhiainen, Alexandra; Psallidas, Ioannis; Wählby Hamrén, Ulrika; Prothon, Susanne (Drug metabolism and disposition, 2022)
This open-label, single-period study describes the human absorption, distribution, metabolism, excretion, and pharmacokinetics of velsecorat (AZD7594). Healthy subjects received inhaled velsecorat (non-radiolabeled; 720 µ g) followed by intravenous infusion of carbon 14 (14C)-velsecorat (30 µ g). Plasma, urine, and feces were collected up to 168 hours post-dose. Objectives included identification and quantification of velsecorat and its metabolites (i.e., drug-related material) in plasma and excreta, and determining the elimination pathways of velsecorat by measuring the rate and route of excretion, plasma half-life (t1/2), clearance, volume of distribution and mean recovery of radioactivity. On average, 76.0% of administered 14C dose was recovered by the end of the sampling period (urine = 24.4%; feces = 51.6%), with no unchanged compound recovered in excreta, suggesting that biliary excretion is the main elimination route. Compared with intravenous 14C-velsecorat, inhaled velsecorat had a longer t1/2 (27 versus 2 hours), confirming that plasma elimination is absorption-rate-limited from the lungs. Following intravenous administration, t1/2 of 14C-drug-related material was longer than for unchanged velsecorat, and 20% of the 14C plasma content was related to unchanged velsecorat. The geometric mean plasma clearance of velsecorat was high (70.7 l/h) and the geometric mean volume of distribution at steady state was 113 l. Velsecorat was substantially metabolized via O-dealkylation of the indazole ether followed by sulfate conjugation, forming the M1 metabolite, the major metabolite in plasma. There were 15 minor metabolites. Velsecorat was well tolerated, and these results support the progression of velsecorat to phase 3 studies. This study describes the human pharmacokinetics and metabolism of velsecorat, a selective glucocorticoid receptor modulator, evaluated via co-administration of a radiolabeled intravenous microtracer dose and a non-radiolabeled inhaled dose. This study provides a comprehensive assessment of the disposition of velsecorat in humans. It also highlights a number of complexities associated with determining human absorption, distribution, metabolism, and excretion for velsecorat, related to the inhaled route, the high metabolic clearance, sequential metabolite formation and the low intravenous dose.